Investigation of the Top Scopus-Indexed Journals in Agricultural and Biological sciences Across Diverse Asian Countries: A Bibliometric Analysis - Maporn, Sattra; Puseerit, Jirarat; Rungwisai, Phakwilai; Arsapar, Panyawat; Chowtivannakul, Pichaya; Photong, Chonlatee (Journal of Applied Informatics and Technology, 2024)
This article presents bibliometric data of major Asian Scopus-indexed journals in agricultural and biological sciences. The study aimed to compare top cited articles published in the top ranked journals in agricultural and biological sciences across different countries. Another purpose is to compare keywords, authors, and country collaboration of in the top ranked journals in agricultural and biological sciences across different countries. The data were collected from two sources, the Scimago Journal Ranking (SJR) 1999-2022 for yearly citation and publications and Scopus database for bibliometric data. The methodology included content analysis and bibliometric analysis of the selected journals, including the top-ranked journals located in China, Japan, and India. The instruments used were fundamental statistics and VOS viewer which was used for crafting author collaboration and keyword map. The analysis revealed that research on the 2019-nCoV virus, plant resilience, and fish genetics received most citations. While keyword analysis revealed similarities in the content of the journals, variations exist in the number of citations and publications. In addition, distinctions arise in authors and international collaboration. Typically, featured authors in each journal are predominantly researchers from the country where the journal is based. Finally, the political standings of each country also affected the publication.